2023
DOI: 10.1111/imj.16145
|View full text |Cite
|
Sign up to set email alerts
|

Risk of venous thromboembolism in COVID‐19 infection

Abstract: The incidence of venous thromboembolism (VTE) for non‐hospitalised patients with coronavirus disease‐2019 infection has not been very widely studied. 13 019 persons with a positive SARS‐CoV‐2 nucleic acid amplification test were identified. In total, 447 (0.2%) VTEs were identified in the study population, 293 (66%) of these were pulmonary embolisms. A positive SARS‐CoV‐2 test did not increase the risk for VTE in the univariate analysis (odds ratio (OR): 1.0, 95% confidence interval (CI): 0.69–1.4) or multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…20 Secondly, pro-inflammatory cytokines release, platelet adhesion and aggregation, endothelial inflammation and injury, thrombin generation caused by SARS-CoV-2 virus infection might lead to immunothrombosis. 21,22 Epidemiologic studies indicated a high incidence of venous thromboembolic events (VTEs), including deep vein thrombosis (DVT) and pulmonary embolism (PE), in patients with COVID-19; [23][24][25] COVID-19 might also be associated with an increased incidence of arterial thrombotic events such as ischemic stroke and limb ischemia, especially in patients with severe COVID-19. [26][27][28] Thirdly, TPO-RA increases platelet production by binding to and activating the thrombopoietin receptor on the membrane of megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%
“…20 Secondly, pro-inflammatory cytokines release, platelet adhesion and aggregation, endothelial inflammation and injury, thrombin generation caused by SARS-CoV-2 virus infection might lead to immunothrombosis. 21,22 Epidemiologic studies indicated a high incidence of venous thromboembolic events (VTEs), including deep vein thrombosis (DVT) and pulmonary embolism (PE), in patients with COVID-19; [23][24][25] COVID-19 might also be associated with an increased incidence of arterial thrombotic events such as ischemic stroke and limb ischemia, especially in patients with severe COVID-19. [26][27][28] Thirdly, TPO-RA increases platelet production by binding to and activating the thrombopoietin receptor on the membrane of megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%